Adenovirus type 35-vectored tuberculosis vaccine has an acceptable safety and tolerability profile in healthy, BCG-vaccinated, QuantiFERON®-TB Gold (+) Kenyan adults without evidence of tuberculosis. Issue 21 (5th May 2016) - Walsh, Douglas S.; Owira, Victorine; Polhemus, Mark; Otieno, Lucas; Andagalu, Ben; Ogutu, Bernhards; Waitumbi, John; Hawkridge, Anthony; Shepherd, Barbara; Pau, Maria Grazia; Sadoff, Jerald; Douoguih, Macaya; et al.
Abstract: In a Phase 1 trial, we evaluated the safety of AERAS-402, an adenovirus 35-vectored TB vaccine candidate expressing 3 Mycobacterium tuberculosis ( Mtb ) immunodominant antigens, in subjects with and without latent Mtb infection. HIV-negative, BCG-vaccinated Kenyan adults without evidence of tuberculosis, 10 QuantiFERON ® -TB Gold In-Tube test (QFT-G)(−) and 10 QFT-G(+), were randomized 4:1 to receive AERAS-402 or placebo as two doses, on Days 0 and 56, with follow up to Day 182. There were no deaths, serious adverse events or withdrawals. For 1 AERAS-402 QFT-G(−) and 1 AERAS-402 QFT-G(+) subject, there were 3 self-limiting severe AEs of injection site pain: 1 after the first vaccination and 1 after each vaccination, respectively. Two additional severe AEs considered vaccine-related were reported after the first vaccination in AERAS-402 QFT-G(+) subjects: elevated blood creatine phosphokinase and neutropenia, the latter slowly improving but remaining abnormal until study end. AERAS-402 was not detected in urine or throat cultures for any subject. In intracellular cytokine staining studies, curtailed by technical issues, we saw modest CD4+ and CD8+ T cell responses to Mtb Ag85A/b peptide pools among both QFT-G(−) and (+) subjects, with trends in the CD4+ T cells suggestive of boosting after the second vaccine dose, slightly more so in QFT-G(+) subjects. CD4+ and CD8+ responses to Mtb antigen TB10.4 were minimal. Increases in Adenovirus 35 neutralizing antibodies from screening to end of study, seen in 50% of AERAS-402 recipients, were mostly minimal. This small study confirms acceptable safety and tolerability profiles for AERAS-402, in line with other Phase 1 studies of AERAS-402, now to include QFT-G(+) subjects.